2020
DOI: 10.1186/s13075-020-02158-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation and correlation between galectin-9 and anti-CCP antibody (ACPA) in rheumatoid arthritis patients

Abstract: Background: Galectin-9 (Gal-9) is involved in the regulatory process of immune responses or inflammation. The aim of the present study is to characterize circulating Gal-9 in patients with rheumatoid arthritis (RA) and its relationship with RA disease activity and phenotype. Methods: A total of 116 RA patients and 31 age-matched healthy controls were included in this study. Disease activity of RA patients was determined by Disease Activity Score of 28 joint scoring system (DAS28-ESR). Levels of Gal-9 in serum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
5
23
0
Order By: Relevance
“…Elevated serum Gal-9 levels have been detected in various autoimmune disease [31][32][33]. Consist with the previous studies in patients with juvenile DM [25,26], our study demonstrated that adult patients with DM exhibited increased serum Gal-9 levels compared to those in HCs.…”
Section: Discussionsupporting
confidence: 83%
“…Elevated serum Gal-9 levels have been detected in various autoimmune disease [31][32][33]. Consist with the previous studies in patients with juvenile DM [25,26], our study demonstrated that adult patients with DM exhibited increased serum Gal-9 levels compared to those in HCs.…”
Section: Discussionsupporting
confidence: 83%
“…We previously demonstrated that circulating Gal-9 is elevated and partly correlated with the titers of autoantibodies in patients with autoimmune diseases [28,29]. However, the more elevated levels of serum galectin-9 were demonstrated and positively correlated with disease activity in an autoinflammatory disease, ASD.…”
Section: Discussionmentioning
confidence: 97%
“…In support of our findings regarding TNF, the in vitro model using IC stimulation of PBMCs resulted in profound TNF production and such IC driven TNF production has been demonstrated previously ( 39 ). Of further interest in this context, two recent studies have reported galectin-9 as a valuable biomarker of disease activity in another TNF-driven disease – namely rheumatoid arthritis (RA) ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%